2020
DOI: 10.1007/s10608-020-10113-4
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Intolerance of Uncertainty and Cognitive Behavioural Instructions on Safety Learning

Abstract: Background Difficulty updating threat associations to safe associations has been observed in individuals who score high in self-reported Intolerance of Uncertainty (IU). Here we sought to determine whether an instruction based on fundamental principles of Cognitive Behavioural Therapy could promote safety learning in individuals with higher levels of IU, whilst controlling for self-reported trait anxiety (STICSA). Methods We measured skin conductance response, pupil dilation and expectancy ratings during an as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 49 publications
0
15
1
Order By: Relevance
“…However, only recently has research began to emerge on the importance of individual differences in IU in associative threat and safety learning mechanisms (27,34). Several studies, albeit from the same laboratory (34), have shown that during threat extinction training, individuals with high IU exhibit greater skin conductance responding (SCR) to cues that no longer signal threat (15,(35)(36)(37)(38)(39). However, presentations of disrupted threat extinction training in individuals with high IU appears varied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only recently has research began to emerge on the importance of individual differences in IU in associative threat and safety learning mechanisms (27,34). Several studies, albeit from the same laboratory (34), have shown that during threat extinction training, individuals with high IU exhibit greater skin conductance responding (SCR) to cues that no longer signal threat (15,(35)(36)(37)(38)(39). However, presentations of disrupted threat extinction training in individuals with high IU appears varied.…”
Section: Introductionmentioning
confidence: 99%
“…(2) greater SCR to learned threat cues versus safety cues during late trials (36,37) or (3) greater SCR to learned threat cues across all trials (15,35). Several studies have also reported no association between IU and SCR during threat extinction training (39)(40)(41).…”
Section: Introductionmentioning
confidence: 99%
“…larger SCR for the CS+ vs. CS-at the beginning of extinction learning, and comparable SCR for the CS+ and CS-at the end of extinction learning. However, in recent preregistered studies with eyetracking, we have only observed significant effects of stimulus on SCR, and no significant interaction between stimulus x time in our control groups, suggesting that participants continue responding to the CS+ vs. CS- (Morriss et al, 2020;Wake et al, 2020). The two recent studies with eyetracking have near identical procedures to older studies without eyetracking.…”
Section: Introductionmentioning
confidence: 41%
“…Prior extinction learning research has shown specificity of IU over self-reported trait anxiety, social anxiety and worry Wake et al, 2021). However, recent published research suggests that STICSA may be more closely related to extinction-learning compared to other self-report measures of anxiety and worry (Morriss et al, 2020;Wake et al, 2020). Future work should continue to include and examine the impact of IU and STICSA upon threat extinction to disentangle shared and specific processes related to these transdiagnostic measures of anxiety (Lonsdorf & Merz, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…Carleton (2016b) defined intolerance of uncertainty as “an individual’s dispositional incapacity to endure the aversive response triggered by the perceived absence of salient, key, or sufficient information, and sustained by the associated perception of uncertainty” (p. 31). Intolerance of uncertainty has been associated with heightened psychophysiological reactivity and conditioning to threat cues (Morriss, Saldarini, & van Reekum, 2019) and impairment of safety learning (Wake, van Reekum, Dodd, & Morriss, 2020).…”
Section: Traits Associated With Health Threat Reactivitymentioning
confidence: 99%